Adult bronchiolitis obliterans in eosinophilic enteritis: a rare association - Subramani, Jayaprakash; Murugan, Mariappan (International Journal of Research in Medical Sciences, 2016)
We hereby present this rare disease in adult with eosinophilic enteritis. This case is reported since there are no published reports of bronchiolitis obliterans (BO) associated with eosinophilic enteritis. A 70yrs. old lady presented with sudden onset of dyspnea which was initially treated as pneumonia with anti-bacterial agents with poor result. She was provisionally diagnosed as small air way disease (Bronchiolitis obliterans) based on imaging and treated with parenteral steroids with empirical anti-bacterial agents. Infective workup was negative. Lung biopsy showed features of bronchiolitis obliterans. She showed partial response to high dose steroid therapy with relapse of severe dyspnea within short period. She was treated successfully with parenteral cyclophosphamide. Bronchiolitis obliterans is a rare cause for acute respiratory failure among adults in India. It manifests as pneumonia-like illness which is poorly responsive to broad spectrum antibiotics. Lung biopsy is usually required to confirm this non-infectious condition. Majority of patients respond to high dose steroid therapy. On rare occasion, steroid resistant cases require cyclophosphamide or cyclosporin therapy. Bronchiolitis obliterans should be considered as a possibility in acute or sub-acute unresolved pneumonia like illness especially in the absence of infective aetiology. Empirical therapy with steroids/ cyclophosphamide should be tried in cases with fatal respiratory failure. Bronchiolitis obliterans associated with eosinophilic enteritis is a novel thing, even though management of BO does not differ in this setting.